Смеховое начало в творчестве Л. Н. Андреева (проза начала 1900-х гг.) - Гомон, Андрей Михайлович (ТОВ "Фінансова Рада України", 2018)
В статье впервые осуществлен анализ ранней прозы Леонида Андреева под смеховым углом зрения. При этом получило подтверждение предположение ученых о смеховом начале как важном константном элементе произведений писателя, во многом определяющем их специфику.

The paper is the first analysis of Andreev’s early prose from laughing point of view where laughing beginning is viewed as an integral component of the writer’s laughing world. As a result of laughing interpretation of Andreev’s prose its genuine innovative character and originality as well as its ideological and aesthetic value is revealed.
A laughter beginning in L. N. Andreev’s creativity (prose of the beginning of the 1900-s years)
Keywords: образ-символ; смех; ирония; гротеск; мотив; image-symbol; laughter; laughing beginning; irony; grotesque; motif